النبوة في الفكر الحداثي - هشام جعيط أنموذجا - شعباني, عمر (University of Eloued جامعة الجزائر, 2020)
"تتناول هذه الدراسة موضوع النبوة في فكر هشام جعيط الحداثي، حيث تعتبر النبوة خبر السماء إلى الأرض بواسطة من اصطفاه االله لحمل رسالته، كما تعتبر الحداثة الغربية ثورة على كل ما هو قديم، وقد انتقلت إلى الوطن العربي بعد رجوع البعثات العلمية العربية من الدول الغربية حاملة أفكارها، و من أبرز أعلامها في المغرب العربي المفكر التونسي هشام جعيط، والذي تتمثل أفكاره حول ّالنبو ُة بالتناقض والاضطراب، حيث تارة يقدس القرآن ويج ّل النبي، وتارة أخرى يطعن وينكر في الثوابت، كقصة الغار وأمية النبي ، وبالتالي فمخرجات الفكر الحداثي عامة لا تمت لفكرنا وثقافتنا العربية والإسلامية بأية صلة""This study deals with the subject of prophethood in the modernist thought of Hisham Jeait, where prophecy is considered the news of heaven to earth by whom God has chosen to carry his message, just as Western modernity is considered a revolution against all that is old, and it moved to the Arab world after the return of Arab scientific missions from Western countries bearing Her ideas, and one of her most prominent figures in the Maghreb, the Tunisian thinker Hisham Djait,And whose ideas about prophethood are represented by contradiction and confusion, as at times the Qur’an sanctifies and reveres the Prophet, and at other times he challenges and denies constants, such as the story of the laurel and the illiteracy of the Prophet, and therefore the outputs of modernist thought in general are not related to our Arab and Islamic thought and culture."
مذكرة ماستر تخصص عقيدة
Keywords: النبوة - الفكر - الحداثي; Prophecy - thought - modernity